2016
DOI: 10.1038/srep32596
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic assembly in a subtropical forest chronosequence: evidence from contrasting changes of species, phylogenetic and functional dissimilarity over succession

Abstract: Deterministic and stochastic processes jointly determine the community dynamics of forest succession. However, it has been widely held in previous studies that deterministic processes dominate forest succession. Furthermore, inference of mechanisms for community assembly may be misleading if based on a single axis of diversity alone. In this study, we evaluated the relative roles of deterministic and stochastic processes along a disturbance gradient by integrating species, functional, and phylogenetic beta div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…From these results they concluded that abiotic filtering strongly dominated the plant community assembly in the early stages of succession and the role of biotic interactions increased in the later successional stages. However, some studies argue that changes in plant phylogenetic community structure during succession may not be caused only by environmental filtering and biotic interactions (deterministic factors), but can also be caused by stochastic factors (Martins et al, ; Mi et al, ). For example, Norden, Letcher, Boukili, Swenson, and Chazdon, () found that demographic processes (mortality and recruitment) drove variation in phylogenetic community structure across successional gradients at different temporal scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results they concluded that abiotic filtering strongly dominated the plant community assembly in the early stages of succession and the role of biotic interactions increased in the later successional stages. However, some studies argue that changes in plant phylogenetic community structure during succession may not be caused only by environmental filtering and biotic interactions (deterministic factors), but can also be caused by stochastic factors (Martins et al, ; Mi et al, ). For example, Norden, Letcher, Boukili, Swenson, and Chazdon, () found that demographic processes (mortality and recruitment) drove variation in phylogenetic community structure across successional gradients at different temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Norden, Letcher, Boukili, Swenson, and Chazdon, () found that demographic processes (mortality and recruitment) drove variation in phylogenetic community structure across successional gradients at different temporal scales. Mi et al, () found weak evidence of deterministic processes (species, functional and phylogenetic turnover) in plant community assembly during forest succession in Southeastern China. They suggested that the weak evidence for deterministic processes detected might result from the prevalence of stochastic processes, particularly priority effects and random immigration.…”
Section: Introductionmentioning
confidence: 99%
“…() inferred the phylogenetic relationships of all European plants from a tree missing major clades including monocotyledons, legumes and sunflowers, casting serious doubts on their conclusions (Davis, Schaefer, Ruhfel, Donoghue, & Edwards, ). While this issue seems especially prevalent in studies of plant communities (e.g., Barber et al., ; Bhaskar, Porder, Balvanera, & Edwards, ; Condit, Engelbrecht, Pino, PĂ©rez, & Turner, ; Funk & Wolf, ; Godoy et al., ; Kress et al., ; Li et al., ; LososovĂĄ et al., ; Marx, Giblin, Dunwiddie, & Tank, ; Matos et al., ; Mi et al., ; Montesinos‐Navarro, VerdĂș, Querejeta, & Valiente‐Banuet, ; Navarro‐Cano et al., ; Pellissier et al., ; PistĂłn, Schöb, Armas, Prieto, & Pugnaire, ; Staab et al., ; Xu et al., ), it is present in animal studies as well (e.g., Arnan, CerdĂĄ, & Retana, ). To determine how prevalent this practice is currently, we surveyed the scientific literature of 2017 using the Boolean search term “community AND (phylogenetics OR phylogeny OR tree).” We included studies that used phylogenetic data (as opposed to taxonomic ranks) and excluded reviews, posters, books, conference abstracts or other non‐peer‐reviewed articles.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the spatial distribution and drivers of woody plants are available. In particular, the effects of abiotic factors, such as topography (Svenning, 1999;Wangda and Ohsawa, 2006;Lan et al, 2011), light (Han et al, 2017;GallĂ© et al, 2018), and soil (Song et al, 2015;Gao et al, 2017), and biological factors, such as competition (Zhu et al, 2015(Zhu et al, , 2018 and species succession (Mi et al, 2016;Sun et al, 2017), on woody plants have been investigated. In the present study, different woody plant species had distinct specific preferences among various plant community types in the temperate mountain forest.…”
Section: Discussionmentioning
confidence: 99%